A-15 Mental Health Practitioners' Immediate Practical Response to the COVID-19 Pandemic. (28th August 2020) - Reilly, S; Zane, K; Mccuddy, W; Soulliard, Z; Scarisbrick, D; Miller, L; Mahoney, J
Abstract: Objective: This paper examined how mental health practitioners adjusted their practices during COVID-19. The authors hypothesized that practitioners would transition services to telehealth but that this would differ by provider type. Method: English-speaking adult mental health practitioners (N = 910) were recruited via professional listservs, personal emails, and social media. Data were collected 03/30/2020–04/10/2020 via an online Qualtrics survey asking about demographics and practice adjustments in response to COVID-19. Most practitioners were psychologists/doctoral-level therapists (41%), social workers/masters-level therapists (17%), and neuropsychologists (16%). The majority was employed in an academic medical center (19%) or private practice (22%). Differences among provider types were examined using chi-square tests with Bonferroni corrections and one-way ANOVAs with post-hoc Tukey tests. Preliminary Results (see Table 1): Most mental health practitioners adjusted their practices, primarily by transitioning to telehealth. The majority reported having easy access to information technology (IT) services. Although telehealth implementation was neutral to somewhat difficult, participants were neutral to somewhat likely to provide telehealth in the future. Compared to other practitioners, neuropsychologists saw fewer patients; were more likely to cancel, reschedule, or restrict appointments; were less likely to implement telehealth; and reported greater difficulty doing so. Findings related to other group differences (e.g., between settings) will also be presented. Conclusions: During the COVID-19 outbreak, mental health practitioners rapidly shifted to telehealth, but neuropsychologists were less likely to do so and reported greater difficulty doing so. This may be related to the difficulty of administering neuropsychological tests remotely and has implications for neuropsychologists' ability to meet patients' needs during COVID-19.